Analisa karakteristik aliran pada fenomena sirkulasi alam fasa-tunggal di Untai FASSIP-01 Mod.2 - Ezer Putra Darmawan, Nathaniel; Heru K, G.B.; Haryanto, Dedy; ., Giarno; Suprapta Winaya, I Nyoman; Sugita, I Ketut Gede; Brahmanda Sudarsana, Putu; Juarsa, Mulya (Jurnal Energi Dan Manufaktur; Vol 14 No 2 (2021), 2022)
FASSIP-01 rectangular loop is a facility which owned by PTKRN-BATAN that used for observe the phenomenon of natural circulation in large-scale. This natural circulation phenomenon will be applied as a passive cooling system in nuclear power plant that will be built up in Indonesia. Some FASSIP-01 experiments have done before, but those experiments show that the fluid flow in FASSIP-01 is not in optimal conditions because there are some errors happened and causes some losses. The second modification of FASSIP-01 rectangular loop has purpose to minimize losses happened in previous modification of FASSIP-01. The purpose of this research is to know the characteristics of flow and the trend of the data from the flow in FASSIP-01 mod.2 rectangular loop before do experiments. Simulations is done by using 2-dimensional images and varying the heating temperature at 353,15 K and 363,15 K and the cooler at temperatures of 278.15 K, 283.15 K, 288.15 K and 293.15 K. Based on the simulation results it is known that the velocity flow rate will increase if the temperature in the heating tank is increased, but will decrease if the temperature in the cooling tank is increased. The results of the calculation of the Reynold Number and Nusselt Number based on the velocity flow rate are 2973,668 the lowest and 5775,356 the highest and for the Nusselt number  obtained 17,36 and the highest is 28,091.